Effect of extrusion on the microstructure and thermomechanical behavior of continuously electromagnetic casting AZ31. (4th September 2019) - Wang, Qiwei; Li, Dan; Yang, Yingfei; Wang, Xiaoming; Chang, Qing; Han, Guofeng; Zhu, Sheng; Li, Wei
Abstract: The thermal deformation behaviour of semi-continuously electromagnetic casting AZ31 magnesium alloy was investigated by compression tests with strain rate controlled for 0.001 ∼ 0.1 s −1 at 473 K ∼ 623 K. A detailed analysis with respect to the influencing parameters was then conducted based on the true stress-strain curve, including calculating the deformation activation energy under various magnetic field conditions. Extrusion tests of AZ31 alloy under different casting conditions were performed. The testing parameters were optimized by the available hot compression data. The fracture morphology of pre- and post-deformation were compared to evaluate the effects of casting conditions on the microstructures and performances of the extrusion bars. The results show that dynamic recrystallization takes place under all the experimental conditions. The stress-strain curve exhibits a peak firstly, and then a drop followed to a stable stage with the subsequent strain accumulation. The value of the stable stage decreases with the increase of temperature but decrease of the strain rate. The dynamic recrystallization leads to a refinement of the grains and hence enhanced the mechanical performance of the materials. In addition, a hereditary effect was found on the properties of the extrusion AZ31 alloys for electromagnetic field frequency.